Burden of coeliac disease in Germany: real-world insights from a large retrospective health insurance claims database analysis - Bernd Bokemeyer; Leonarda Serdani-Neuhaus; Juliane Sünwoldt; Christina Dünweber; Svitlana Schnaidt; Detlef Schuppan (Therapeutic Advances in Gastroenterology)
Background: Coeliac disease (CeD) is a chronic immune-mediated disease triggered by exposure to dietary gluten in genetically predisposed individuals. The burden of CeD on patients and the healthcare system remains poorly evaluated in Germany. Objectives: To assess the healthcare resource utilisation (HCRU) and costs of diagnosed CeD patients in a German claims database. Design: A retrospective CeD case–control study was conducted using German claims data between 2017 and 2021. Methods: CeD diagnosis was defined by at least one inpatient or two outpatient diagnostic codes (International Statistical Classification of Diseases and Related Health Problems, 10th Revision, German Modification (ICD-10-GM) K90.0) within four quarters (irrespective of calendar year) for CeD during the study period. Controls (non-CeD patients) were matched in a ratio of 5:1 by age, Charlson Comorbidity Index, sex and region. HCRU (hospitalisations, outpatient visits, medication use, sick leaves) and healthcare costs (outpatient services, inpatient services, outpatient pharmaceuticals, sick leaves and aids and remedies) were compared between CeD patients and controls. Results: From the 3,352,188 patients with continuous enrolment during the study period (2017–2021), 8258 (0.25%) patients were identified as having a CeD diagnosis. The mean number of hospitalisations and outpatient visits within 5 years was 1.8- and 1.5-fold higher among matched CeD patients ( n = 8243) compared to their controls ( n = 41,215), resulting in an excess healthcare cost of €5251. Inpatient expenses were the main cost driver and accounted for 31.5% of total incremental costs. Conclusion: The current study showed that CeD patients have considerably higher HCRU and related costs compared to matched controls. Our findings suggest the need for improved treatment options for CeD patients in addition to a gluten-free diet.